Estrutura das comunidades fitoplanctônica e zooplanctônica, com ênfase na produção secundária do zooplâncton, e fatores ambientais relacionados nos reservatórios do Baixo rio Tietê, SP - Santos, Renata Martins dos (Universidade Federal de São Carlos, 2010)
The present study aimed to analyze the zooplankton community dynamics and its relationships environmental factors in Promissão, Nova Avanhandava and Três Irmãos reservoirs placed in the Low Tietê River sub-basin, SP, Brazil. It also had the objective of analyzing patterns of spatial and temporal fluctuations in density, biomass and secondary production of the zooplankton community. Sampling in each reservoir was carried out in a fixed point, at three depths in the water column: surface, intermediate and bottom layers, during four periods: July and September 2008 (dry period) and January and May 2009 (rainy period). Main physical and chemical variables were measured in situ and samples of water were taken for laboratory measurements of nutrients, suspended matter and chlorophyll a. Quantitative phytoplankton and zooplankton samples were collected with a motorized suction pump and filtered through plankton nets. The taxonomical composition and numerical density of both communities were determined and the biomass and secondary production of zooplankton were quantified. Zooplankton organisms were sorted out by species, measured regarding sizes and biomasses and had their secondary production estimated. Biomass and production were calculated for Rotifera, Cladocera and Copepoda using different methodologies according to the taxonomical group. Results obtained evidenced that all three reservoirs were oligotrophic, although the first two with tendency to mesotrophy. The highest values of density and production occurred in the rainy period. The maximum zooplankton production was 51,671.4 μg DW. m-3.day-1) in Promissão Reservoir in September, 2008. P:B ratio varied from 0.01 to 1.91 for Rotifera; from 0.01 to 2.14 for Cladocera and from 0.15 to 3.13 for Copepoda. Rotifera were numerically dominant, but Copepoda dominated in biomass and secondary production. There is a decrease in trophic state and an increase in water quality from the first (Promissão) to the third reservoir (Três Irmãos). Hydrological factors (discharge and water residence time), climatic factors (mainly temperature and precipitation) and biological (food quality and availability) were the main factors controlling zooplankton fluctuations. Zooplankton production was one order of magnitude higher in Promissão and Nova Avanhandava than in Três Irmãos Reservoir.
Keywords: Ecologia; Ecologia dos reservatórios; Zooplâncton; Produção secundária (Biologia); Fitoplâncton; Tietê, Rio, Bacia (SP); CIENCIAS BIOLOGICAS::ECOLOGIA